Artificial intelligent towards hotels’ competitive advantage. An exploratory study from the UAE - Al-Shami, Samer Ali Hussein; Al Mamun, Abdullah; Ahmed, Elsadig Musa; Abdul Rashid, Nurulizwa (Emerald Publishing Limited, 2022)
Purpose – Hotel industry is witnessing a radical change as a result of technology interaction such as artificial intelligence (AI) in service tasks. As a result of this transformation, the pattern of service delivery based on human interaction has been changed to digital interaction. This brought opportunities to the hotels industry and consolidate its competitive advantage. However, the understanding gap still existed in both practical implementation and literature, especially in developing countries. Therefore, this paper aims to explore how hotels use AI to carry out services tasks. Design/methodology/approach – The authors adopted the qualitative research method through Semi interviews. The sample was purposively selected from five 5-star hotels in the UAE, meanwhile, the managers were the targeted respondents. Findings – Through content analysis, the authors find that the UAE hotels use AI in managing trip planning, reception service and room services. The authors also find that there are four key drivers that improve the performance of AI, which include AI infrastructure flexibility, strategic alignment, management and skills. Finally, the authors found four indicators of the impact of AI on hotels, which are quality, cost and market share and customers satisfaction. Originality/value – This study is one of few studies that explored the use of AI in the hotels industry and discussed how AI influence several aspects of hotels performance and helped them to attain their competitive advantage. This study is also one of few studies and the first study in UAE to explore the key drivers of AI performance in UAE hotels